Nitrous oxide emissions in pineapple cultivation on a tropical peat soil - Jeffary, Alicia Vanessa; Ahmed, Osumanu Haruna; Kueh, Roland Jui Heng; Lim, Liza Nuriati Kim Choo; Omar, Latifah; Alhassan Musah, Adiza; Abdu, Arifin (MDPI, 2021)
Farming systems on peat soils are novel, considering the complexities of these organic soil. Since peat soils effectively capture greenhouse gases in their natural state, cultivating peat soils with annual or perennial crops such as pineapples necessitates the monitoring of nitrous oxide (N2O) emissions, especially from cultivated peat lands, due to a lack of data on N2O emissions. An on-farm experiment was carried out to determine the movement of N2O in pineapple production on peat soil. Additionally, the experiment was carried out to determine if the peat soil temperature and the N2O emissions were related. The chamber method was used to capture the N2O fluxes daily (for dry and wet seasons) after which gas chromatography was used to determine N2O followed by expressing the emission of this gas in t ha−1 yr−1. The movement of N2O horizontally (832 t N2O ha−1 yr−1 ) during the dry period was higher than in the wet period (599 t N2O ha−1 yr−1 ) because of C and N substrate in the peat soil, in addition to the fertilizer used in fertilizing the pineapple plants. The vertical movement of N2O (44 t N2O ha−1 yr−1) was higher in the dry season relative to N2O emission (38 t N2O ha−1 yr−1) during the wet season because of nitrification and denitrification of N fertilizer. The peat soil temperature did not affect the direction (horizontal and vertical) of the N2O emission, suggesting that these factors are not related. Therefore, it can be concluded that N2O movement in peat soils under pineapple cultivation on peat lands occurs horizontally and vertically, regardless of season, and there is a need to ensure minimum tilling of the cultivated peat soils to prevent them from being an N2O source instead of an N2O sink.